Pengembangan Kompetensi Profesional Guru Sebagai Upaya Meningkatkan Hasil Pembelajaran Peserta Didik Di SMAN 1 Manonjaya Kabupaten Tasikmalaya - Ida Hendarti (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Education is an important component in a nation, if education is advanced then the nation will become strong and able to compete. On the other hand, if education is weak, it will be weak too. So that the teacher's role is so important in transforming educational inputs, student learning outcomes will then become one of the standard indicators determining the level of professionalism of a teacher. Therefore, the development of teacher professional competence is very important to do. The research approach used is a qualitative approach, which is carried out in certain settings in real life. Qualitative research is rooted in a natural setting as a whole, relying on humans as a research tool, utilizing qualitative methods, conducting inductive data analysis, directing the target to discovering theories from basic, descriptive. Teachers at SMAN 1 Manonjaya have sufficient professional competence in the average category. The condition of learning outcomes in general can be seen in the average anyway. The general objective description of the learning outcomes of students at SMAN 1 Manonjaya is seen from the results of the average school exam scores in the last 3 years. The learning process is certainly very dependent on the teacher who teaches. The more effective the learning process carried out by the teacher, of course it will have a positive impact on students which will also have an impact on the quality of graduates.